2012
DOI: 10.3390/ijms13055751
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin-Induced Cytotoxicity, Oxidative Stress and Mitochondrial Dysfunction in Human Hepatoma HepG2 Cells

Abstract: Streptozotocin (STZ) is an antibiotic often used in the treatment of different types of cancers. It is also highly cytotoxic to the pancreatic beta-cells and therefore is commonly used to induce experimental type 1 diabetes in rodents. Resistance towards STZ-induced cytotoxicity in cancer cells has also been reported. Our previous studies have reported organ-specific toxicity and metabolic alterations in STZ-induced diabetic rats. STZ induces oxidative stress and metabolic complications. The precise molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 31 publications
7
68
0
Order By: Relevance
“…Previous studies showed that decomposition of STZ leads to formation of both superoxide and nitric oxide (NO) (33)(34)(35). As these two react in a diffusion-controlled manner to form peroxynitrite (36), which is known to oxidize cysteines forming sulfenic acid and/or disulfides (37), we examined a direct reaction of STZ with cysteines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that decomposition of STZ leads to formation of both superoxide and nitric oxide (NO) (33)(34)(35). As these two react in a diffusion-controlled manner to form peroxynitrite (36), which is known to oxidize cysteines forming sulfenic acid and/or disulfides (37), we examined a direct reaction of STZ with cysteines.…”
Section: Resultsmentioning
confidence: 99%
“…Decomposition of STZ could lead to superoxide and finally H 2 O 2 (Scheme 1-i) (35,59), which is a two-electron oxidant known to activate TRPA1 channels (17). However, STZ decomposes to give both NO and superoxide (33)(34)(35)59), which are known to react in a diffusion-controlled manner to give peroxynitrite, a powerful oxidant that could produce all the cysteine modifications that we observed, i.e. cysteinyl radical, sulfenic acid, and disulfides (Scheme 1-ii) (37).…”
Section: Discussionmentioning
confidence: 99%
“…ROS in different tissues of control and CS-treated mice was measured using DCFDA as a fluorescent probe as described before [7,12,13,17]. …”
Section: Methodsmentioning
confidence: 99%
“…Patients with insulin resistance or T2D also manifest decreased mitochondrial density, oxidative activity, and mitochondrial ATP synthesis [9,10]. A study on STZ-diabetic rats showed a persistent increase in reactive oxygen and nitrogen species (ROS and RNS, respectively) production and a decrease in the activities of the mitochondrial respiratory enzymes including ubiquinol-cytochrome c oxidoreductase (complex III) and cytochrome c oxidase (complex IV) [11]. Thus, increasing mitochondrial mass and oxidative activity is viewed as a potential therapeutic approach for the treatment of insulin resistance and diabetes, and minimizes the complications of diabetes or both [12].…”
Section: Introductionmentioning
confidence: 99%